Xanthophyll Accumulation Protects Mice from Influenza Virus Infection Potentially Through SirT3. (29th May 2020) - Lu, Peiran; Wong, Siau Yen; Wu, Lei; Montgomery, Mckale; Chowanadisai, Winyoo; Lucas, Edralin; Smith, Brenda; Clarke, Stephen; Lin, Dingbo
Abstract: Objectives: Seasonal influenza virus infection is one of the top health concerns worldwide. The beta-carotene oxygenase 2 (BCO2) knockout mice are more resistant to virus infection compared to wildtype. We sought to investigate the effects of xanthophylls, e.g., zeaxanthin (Z) and astaxanthin (A) in the regulation of the host innate immune responses to influenza A virus infection in mice. Methods: Six-week-old male and female 129S6 wild type (WT), beta-carotene oxygenase 2 (BCO2) knockout mice, and BCO2/SIRT3 double knockout (DKO) mice were fed with AIN93M chow diets supplemented with or without Z (0.02% w/w) and A (0.02 w/w) (e.g., Z+A). After 5 weeks of the dietary intervention, mice were intranasally infected with 100 pfu H1N1 PR8 virus. Animal body weight and phenotypes were monitored daily. Animals were sacrificed 6 days post-infection. Blood and lung tissues were collected for experiments. H & E staining, ELISA, immunohistochemistry, and immunoblotting were used for clinical, histopathological, and other biochemical assessments. Further, primary mouse embryonic fibroblasts (MEF) cells were isolated from above three mouse strains. Mitochondrial superoxide was detected by MitoSOX TM live cell staining. Poly (I: C) was used to mimic virus infection in MEF cells. Results: Much more significant body weight loss, lung damage, and cytokine storm occurred in WT and DKO mice after virus infection, as compared to the KO. Supplementation of Z+A significantly rescued the pathophenotypes in infected mice, particularly in KO mice. Basal mitochondrial superoxide levels were significantly higher in MEF cells of KO and DKO, compared to the MEF cells from WT mice. The eukaryotic initiation factor 2 α-subunit level was significantly elevated in MEF cells of WT and DKO, after Poly (I: C) stimulation, compared to KO MEF cells. Application of Z at 0.625 μM significantly decreased mitochondrial superoxide levels in KO MEF cells. Conclusions: BCO2 deficiency-associated xanthophyll accumulation protects animals and MEF cells from influenza virus pneumonia and mitochondrial superoxide production. The effects are at least partially through Sirt3. Funding Sources: This work was funded by grants from the Oklahoma Center for the Advancement of Science & Technology and the Oklahoma Agricultural Experiment Station.